2020
DOI: 10.1055/a-1130-4703
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization and Targeted Metabolic Evaluation of Endophytic Fungi Harbored in 14 Seed-Derived Hypericum Species

Abstract: Medicinal plants of the genus Hypericum are rich sources of bioactive naphthodianthrones, which are unique in the plant kingdom, but quite common in fungal endophytes. Cultivable endophytic fungi were isolated from 14 different Hypericum spp. originating from seeds grown under in vitro conditions and further acclimated to outdoor conditions. Among 37 fungal isolates yielded from the aerial and underground plant organs, 25 were identified at the species level by the fungal barcode marker internal transcribed sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The studied fungal endophytes were isolated from hypericin-accumulating aerial tissues of several Hypericum representatives, except for the isolate 8RF1-3 from H. humifusum roots. Our previous results indicated that fungal endophytes are able to produce the same anthraquinones as the host plants [ 5 , 7 , 9 ]. The genome-mining of Hypericum- borne fungal endophytes led to the prediction of candidate biosynthetic gene clusters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studied fungal endophytes were isolated from hypericin-accumulating aerial tissues of several Hypericum representatives, except for the isolate 8RF1-3 from H. humifusum roots. Our previous results indicated that fungal endophytes are able to produce the same anthraquinones as the host plants [ 5 , 7 , 9 ]. The genome-mining of Hypericum- borne fungal endophytes led to the prediction of candidate biosynthetic gene clusters.…”
Section: Resultsmentioning
confidence: 99%
“…were selected based on their ability to produce anthraquinones and bisanthraquinones innate to the host plants. The experimental group comprised two Fusarium oxysporum isolates varying in metabolite production, Scedosporium apiospermum, Plectosphaerella cucumerina, and Diaporthe eres which were collected from plants acclimated to outdoor conditions in the Botanical Garden of Pavol Jozef Šafárik University in Košice, Slovakia [ 9 ] (Table 3 ). The cultures were identified by molecular markers ITS rDNA and protein-coding gene region of tef1α.…”
Section: Methodsmentioning
confidence: 99%
“…Skyrin (7) and its precursors are not abundantly available in plants, but these compounds are produced by different classes of endophytic filamentous fungi [ 34 ]. It could be possible that Hypericum plant-associated endophytes produce these metabolites in planta and contribute to hypericin production, given that endophytes are known to produce secondary metabolites found in their host plants [ 23 , 35 ]. Besides, native endophytes might have acquired the skyrin (7) producing gene machinery through horizontal gene transfer in the course of co-evolution with Hypericum host plants.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, skyrin (7) is typically biosynthesized by fungi belonging to different species and ecological niches and reported to have antimicrobial properties [ 19 , 20 ]. Thus far, the role of plant-associated microorganisms such as endophytes in the production of skyrin (7) is a plausible, open question, particularly since native endophytes harbored in H. perforatum can produce hypericin (6) [ 21 , 22 , 23 ]. Therefore, it is essential to identify the in planta site of localization and the role of skyrin (7) , as well as the related intermediates leading to the production of hypericin (6) .…”
Section: Introductionmentioning
confidence: 99%
“…Both techniques have been used to separate, identify and quantify series of structurally different SMs in plants include spectrophotometric [57,[73][74][75], GC-MS [56,76], LC-MS [77], LC-MS/MS [56,76,78], Liquid Chromatography-High Resolution Electrospray Ionization Mass Spectrometry (LC-HRESIMS) [57], Nuclear Magnetic Resonance (NMR) [44,79], Ultra-Fast Liquid Chromatography (UFLC-Q-TOF-MS/MS) [80][81], UFLC-triple-Q-TOF-MS/MS [82], Ultra-high performance Liquid Chromatography quadrupole-time of flight mass spectrometry [83], UHPLC-LTQ-Orbitrap [84], UHPLC/Q-Orbitrap-MS [85], HPLC-DAD [86], UHPLC-Q-TOF-MS [87], UHPLC-Q-TOF-MS/MS [88], HPLC-DAD-ESI-MS [89], UPLC-QTOF/MSE [90], UHPLC-MS/MS [91], HPLC-ESI-QTOF-MS [92], UPLC-QTOF-MS/MS [93], UHPLC-Q-TOF-MS/MS [94][95], UHPLC-ESI-MS/MS [96], UHPLC-ESI-Orbitrap-MS/MS [97], UPLC-IT-MS [98], UPLC-Q-TOF-MS [98], UPLC-PDA [45], HPLC-ESI-MS and MS 2 [99], reverse phase high performance liquid chromatography-diode array detector (RP-HPLC-DAD) [74], HPLC-HRMS [100]. been used to produce a yellow color that turn colorless on addition of dilute hydrochloric acid confirm flavonoid [102,[104][105]…”
Section: Techniques For Identify and Quantifying Secondary Metabolitesmentioning
confidence: 99%